[HDL‐C/apoA‐I]: A multivessel cardiometabolic risk marker in women with T2DM. Issue 1 (16th October 2017) - Hermans, Michel P.; Valensi, Paul; Ahn, Sylvie A.; Rousseau, Michel F.
Abstract: Aims: Although women have higher high‐density lipoprotein cholesterol (HDL‐C) than have men, their HDL particles are also prone to become small, dense, and dysfunctional in case of type 2 diabetes mellitus (T2DM). To assess the vascular risk related to HDLs of different sizes/densities without direct measurement, we adjusted HDL‐C to its main apolipoprotein (apoA‐I) as [HDL‐C/apoA‐I]. This ratio estimates HDL sizes and provides indices as to their number, cholesterol load, and density. Methods: We stratified 280 Caucasian T2DM women according to [HDL‐C/apoA‐I] quartiles (Q) to determine how they are segregated according to cardiometabolic risk, β‐cell function, glycaemic control, and vascular complications. Five parameters were derived from combined determination of HDL‐C and apoA‐I: HDL size, HDL number, cholesterol load per particle ( p P), apoA‐I p P, and HDL density. Results: An adverse cardiometabolic profile characterized QI and QII patients whose HDLs were denser and depleted in apoA‐I, whereas QIII patients had HDLs with characteristics closer to those of controls. QIV patients had HDLs of supernormal size/composition and a more favourable phenotype in terms of fat distribution; insulin sensitivity (64% vs 41%), metabolic syndrome, and β‐cell function (32% vs 23%); exogenous insulin (44 vs 89 U·d −1 ); and glycaemic control (glycated haemoglobin, 56 vs 61 mmol·mol −1 ), associated with lower prevalence of microvascular/macrovascular complications: all‐cause microangiopathy 47% vs 61%; retinopathy 22% vs 34%; all‐cause macroangiopathy 19% vs 31%; and coronary artery disease 6% vs 24% ( P  < .05). Conclusion: [HDL‐C/apoA‐I] can stratify T2DM women according to metabolic phenotype, macrovascular and coronary damage, β‐cell function, microangiopathic risk, and retinopathy. This ratio is a versatile and readily available marker of cardiometabolic status and vascular complications in T2DM women.